Evaluating AI-Generated Fatwas: A Quality Assessment of ChatGPT and Google Bard Against Authoritative Islamic Rulings - Billah, Mu'tashim; Azhari, Susiknan; Baroroh, Nurdhin; Rahma, Vivi (UIN Sunan Kalijaga, 2023)
The use of Artificial Intelligence (AI) in Islamic law has become a global phenomenon, including in Muslim countries such as the United Arab Emirates and Egypt. AI technology began to go viral when ChatGPT and Google Bard were released, claiming to be able to reason like humans. The development of Natural Language Processing (NLP) technologies like ChatGPT and Google Bard has raised a new question: Can AI replace the role of muftis in issuing fatwas? This qualitative study analyzes the capacity of AI as a fatwa issuer by testing ChatGPT and Google Bard with specific prompts related to Islamic law. The results are compared with official fatwas from Nahdlatul Ulama (NU) and Muhammadiyah, which serve as authoritative fatwa standards in Indonesia. Based on the discussion, this article finds that to date, AI NLP technology is unable to reason Islamic law as a mufti would. Therefore, AI technology cannot yet replace the role of a mufti in issuing fatwas. The main reason is that the credibility and authority of fatwas generated by AI technology cannot be guaranteed. Therefore, the use of AI technology as a fatwa issuer is not recommended. Pemanfaatan Artificial Intelligence (AI) dalam bidang hukum Islam telah menjadi fenomena global, termasuk di negara-negara Muslim seperti Uni Emirat Arab dan Mesir. Teknologi AI mulai sangat viral ketika Chat GPT hingga Google Bard dirilis yang diklaim mampu berpikir layaknya bahasa manusia. Fenomena perkembangan Natural Language Processing (NLP) seperti ChatGPT dan Google Bard memicu pertanyaan baru: Dapatkah AI menggantikan peran mufti dalam berfatwa? Penelitian kualitatif ini menganalisis kapasitas AI sebagai pemberi fatwa melalui uji coba terhadap ChatGPT dan Google Bard dengan prompt spesifik terkait hukum Islam. Hasilnya dibandingkan dengan fatwa resmi Nahdlatul Ulama (NU) dan Muhammadiyah sebagai standar fatwa yang otoritatif di Indonesia. Berdasarkan hasil pembahasan, artikel ini menemukan bahwa hingga saat ini, teknologi AI NLP tidak mampu melakukan nalar hukum Islam sebagaimana seorang nalar seorang mufti. Dengan begitu, teknologi AI belum mampu menggantikan peran seorang mufti untuk berfatwa. Alasan utamanya adalah bahwa hasil fatwa yang digenerate oleh teknologi AI tidak dapat dipertanggungjawabkan kredibilitas dan otoritasnya. Sehingga penggunaan teknologi AI sebagai pemberi fatwa tidak direkomendasikan.